Time-resolved measurement of gas parameters inside diffusion-cooled CO 2 lasers with NIR diode laser and UV-VIS emission spectroscopy - Engelbrecht, Rainer; Schulz, J (SPIE, Vol. 4184 (XIII Int. Symp. on Gas Flow and Chemical Lasers and High Power Laser Conference, Florenz 2000), 2001)
Time-resolved gas dissociation inside diffusion-cooled RF excited CO2 lasers was measured with NIR laser absorption spectroscopy and UV-VIS emission spectroscopy. Roto-vibrational temperatures were derived directly in the discharge region. Effects of gas additives on the plasma processes were studied. © (2001) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
lhft_intern.bib::engelbrecht00a